Street Children's Experience in Maintaining Reproductive Health - Dwi Prima Hanis Kusumaningtiyas; Blacius Dedi; Oop Ropei (Universitas Triatma Mulya, 2019)
Introduction. Street children are children who spend most of their time doing day-to-day activities on the streets, including in the market environment, shops and other hubs. Street children are less concerned about their own health. Access to health services is good for children less than normal people. It affects their health behavior style. This study aims to deeply exploit the juvenile street children's experience in maintaining reproductive health in the Bahtera Child Protection Home Foundation Bandung City. Methods. This research is a qualitative research with phenomenology approach. Participants in this study are adolescent street children under the auspices of the Bahtera Child Protection Home Foundation Bandung City with a total of 7 people. Data collection by indepth interview. Data analysis using thematic analysis according to Collaizzi's method. Results. The research result are six themes; The experience of get reproductive health knowledge, Behavior of reproductive hygiene, Food intake, Drug dependence behavior, psychotropic, and addictive substances, Forms of social violence